Pendidikan Agama Islam bagi Siswa di Keluarga, Sekolah dan Masyarakat: Studi Fenomenologi pada Siswa SMA di Kota Bandung - Endis Firdaus; Agus Fakhruddin; milda ldp (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2023)
Islamic Religious Education in the context of formal education in Indonesia has been part of the national education system since the era of independence. Islamic Religious Education is one of the important elements in education in order to achieve the goals of national education as stated in Law no. 20 of 2003. In the process, religious education obtained by a student will not be separated from three educational environments, namely religious education in the family, at school, and in the community. Researchers try to capture the phenomenon of Islamic Religious Education for Students in Families, Schools, and Communities to be able to answer whether there is meaning obtained by students by utilizing these three educational environments, especially in Islamic Religious Education. Basically, this research is intended to find out the extent to which students get Islamic Religious Education in these three environments and find out whether students can take meaning in learning Islamic Religious Education. The research approach used is qualitative with phenomenological method. In accordance with the approach, that the end of this research will only lead to the positivity paradigm. As John Creswell explains that the phenomenological approach means letting the symptoms that are realized reveal themselves. Data or information acquisition was carried out on high school students in Bandung City. The results showed that students' experiences in receiving Islamic Religious Education in families, schools, and communities were different. Religious education in the family is more emphasized on moral and ethical values, while at school it is more focused on understanding the teachings of Islam. Meanwhile, in the community, students' experiences are more likely to be influenced by the surrounding environment which does not always support a correct understanding of Islam.